Non-thermal plasma application enhances the recovery of transected sciatic nerves in rats. Issue 11 (June 2021) - Lee, Sung-Tak; Jang, Yoon-Seo; Kim, Uk-Kyu; Kim, Hyung-Joon; Ryu, Mi-Heon; Kim, Gyoo-Cheon; Hwang, Dae-Seok
This experimental research aimed to investigate the effects of non-thermal plasma on nerve regeneration after transected nerve damage using the sciatic nerve in Wistar albino (A) rats. The experiments were performed on 27 Wistar A rats. The rats underwent surgery for right sciatic nerve exposure and were divided into three groups (each group, n  = 9) according to sciatic nerve transected injury (SNTI) and non-thermal plasma application: a non-nerve damage (non-ND) group, a only nerve damage without non-thermal plasma application (ND) group, and a nerve damage with non-thermal plasma application (ND + NTP) group. Subsequent to SNTI and immediate suture, non-thermal plasma was administered three times per week for eight weeks. Evaluation for functional recovery was performed using the static sciatic index measured over the full treatment period of eight weeks. The sciatic nerve specimens were obtained after euthanasia and third day from the last non-thermal plasma application. The sciatic nerve tissues were subjected to histological analysis. Behavior analysis presented that the ND + NTP group showed improved static sciatic index compared with the nerve damage group. Histopathological findings demonstrated that the ND + NTP group had more dense Schwann cells and well-established continuity of nerve fibers, greater than the nerve damage group. Immunohistochemistry showed that the ND + NTP group had increased levels of markers for microtubule-associated protein 2 (MAP2), tau, S100 calcium-binding protein B, and neurofilament-200 and regulated the overexpression of CD68 and MAP2. These results indicated that non-thermal plasma enhanced the motor function and restored the neuronal structure by accelerating myelination and axonal regeneration. Additionally, non-thermal plasma was confirmed to have a positive effect on the recovery of SNTI in rats.